Influenza Aviar ("gripe del pollo") (VITAE Academia Biomédica Digital, 2004)
• La gripe aviar («gripe del pollo») y la importancia de su transmisión al ser humano• Avian influenza ("bird flu") and the significance of its transmission to humans• Avian influenza frecuently asked questions• Avian influenza and human health• Human disease from influenza A (H5N1), Thaland, 2004